The investigation of unbalanced vibration in flexible motorized spindle-rotor system. Issue 3 (2nd July 2016) - Qiao, Xiaoli; Hu, Guojun
ABSTRACT: Unbalance is a significant concern for spindle-rotor dynamic systems and an important problem in high-speed machining. An active control scheme with built-in force actuator is proposed for unbalanced vibration of flexible motorized spindle-rotor, which is to improve the performance of high-speed machining system. At first, the motorized spindle motor with built-in force actuator and flexible motorized spindle-rotor are designed and then the experiment setup based on digital signal processor for controlling actively the unbalanced vibration of flexible spindle-rotor is tailored. Finally, the active vibration control scheme is investigated experimentally based on previous theoretical studies. The experimental results prove the feasibility of the active control scheme.